THE PROFESSIONAL ORIENTATION - ELEMENT OF THE SOCIO-PROFESSIONAL INTEGRATION OF THE PERSONALITY OF THE FUTURE PHYSICAL EDUCATION AND SPORT TEACHER - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The professional orientation of the future physical and sport education teacher is continued inside the frame of the instructive-educational development process, which takes place in Physical and Sport Education Faculty, through education plans detailed on the years of study and through analytical programs detailed on disciplines. This orientation is based on the development of the interests, aptitudes and skills formation of the future teacher guaranteeing in the same time the emergence of his personality, as an essential feature of his socio-professional integration, by bringing into relief his physical, intellectual and moral potential.